2019
DOI: 10.1007/s12192-019-00996-y
|View full text |Cite
|
Sign up to set email alerts
|

Salinity stress-induced differentially expressed miRNAs and target genes in sea cucumbers Apostichopus japonicus

Abstract: Environmental salinity is an important abiotic factor influencing normal physiological functions and productive performance in the sea cucumber Apostichopus japonicus. It is therefore important to understand how changes in salinity affect sea cucumbers in the face of global climate change. In this study, we investigated the responses to salinity stress in sea cucumbers using mRNA and miRNA sequencing. The regulatory network of mRNAs and miRNAs involved in salinity stress was examined, and the metabolic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 89 publications
3
14
0
Order By: Relevance
“…Small RNA libraries were constructed and sequenced by a high-throughput sequencing method (on an Illumina HiSeq 2500 platform) at Novogene (Beijing, China), according to previously published methods [53]. Quality control and analysis of sequencing data were also performed by Novogene using methods described previously [54,55]. The miRBase (version 22) was used as a reference to search for known miRNAs by software miRDeep2, and srna-tools-cli was used to obtain the potential miRNAs and draw the secondary structures [56].…”
Section: Small Rna Library Construction Sequencing and Data Analysismentioning
confidence: 99%
“…Small RNA libraries were constructed and sequenced by a high-throughput sequencing method (on an Illumina HiSeq 2500 platform) at Novogene (Beijing, China), according to previously published methods [53]. Quality control and analysis of sequencing data were also performed by Novogene using methods described previously [54,55]. The miRBase (version 22) was used as a reference to search for known miRNAs by software miRDeep2, and srna-tools-cli was used to obtain the potential miRNAs and draw the secondary structures [56].…”
Section: Small Rna Library Construction Sequencing and Data Analysismentioning
confidence: 99%
“…A total of 548 miRNA were identified during low-salinity adaptation, and 22 miRNAs were significantly up-regulated and 34 were significantly down-regulated, indicating that miRNAs are differentially regulated to deal with hypoosmotic stress by R. canadum. Previous studies have shown that miRNAs are widely involved in the adaptation of salinity change in fish and other species via silencing complexes, which can lead to cleavage of target genes or inhibition of translation of the target genes (Flynt et al, 2009;Tian et al, 2019;Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that miRNAs play important roles in many biological processes, such as signal transduction, organ development, immunity, tumorigenesis, metabolism, cell proliferation and apoptosis and so on (Deng et al, 2016;Jung et al, 2019;Lin et al, 2020;Png et al, 2012;Suzuki, 2018;Tian et al, 2019;Yuan et al, 2015).…”
Section: Micrornas (Mirnas) Are a Class Of Single-stranded Non-codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic processes allow organisms to grow and reproduce, maintain their structure, and respond to the external environment. Changes in metabolic patterns among environments are typically related to the pathways of energy production and consumption, including the amino acid metabolism, the carbohydrate metabolism, the fatty acid metabolism, the nucleotide metabolism, membrane transport, protein synthesis and protein digestion (Abdel‐Tawwab & Wafeek, 2017; Das & Majhi, 2015; Tian et al., 2019; Younis, 2015). Thus, changes in the abundance of various metabolites can help to clarify the energy changes associated with different light intensities.…”
Section: Introductionmentioning
confidence: 99%